2022
DOI: 10.3390/biomedicines10092222
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Maternal Fever and Neonatal Sepsis: A Retrospective Study at a Medical Center

Abstract: Various risk factors are associated with neonatal sepsis; however, its relationship to maternal postpartum fever is unknown. This study aimed to determine the relationship between maternal postpartum fever and neonatal sepsis. Full-term and late preterm stable infants born from January 2019 to June 2021 and whose mothers developed intra- or post-partum fever were included in the study. After the newborns were transferred to the nursery, laboratory assessments were performed. Based on clinical conditions and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, several pieces of evidence have indicated that clinical characteristics and other risk factors may propose an important role in determining the odds of bacteriologic confirmation among clinically suspected neonatal sepsis. [3][4][5][6][7] Preterm delivery, 5,6 low-birth-weight, 3,5 low Apgar score, 3,5 mechanical ventilation, 3 cesarean section delivery, 4,5 premature rupture of membranes 3 and intrapartum fever 7 have been previously associated with culture-positive neonatal sepsis.…”
mentioning
confidence: 99%
“…In addition, several pieces of evidence have indicated that clinical characteristics and other risk factors may propose an important role in determining the odds of bacteriologic confirmation among clinically suspected neonatal sepsis. [3][4][5][6][7] Preterm delivery, 5,6 low-birth-weight, 3,5 low Apgar score, 3,5 mechanical ventilation, 3 cesarean section delivery, 4,5 premature rupture of membranes 3 and intrapartum fever 7 have been previously associated with culture-positive neonatal sepsis.…”
mentioning
confidence: 99%